Application of a Laser-Based Time Reversal Algorithm for Impact Localization in a Stiffened Aluminum Plate - Miniaci, Marco; Mazzotti, Matteo; Radzieński, Maciej; Kudela, Pawel; Kherraz, Nesrine; Bosia, Federico; Pugno, Nicola M.; Ostachowicz, Wieslaw (Frontiers in Materials, 2019)
Non-destructive testing and structural health monitoring techniques using elastic guided waves are often limited by material inhomogeneity or geometrical irregularities of the tested parts. This is a severe restriction in many fields of engineering such as aerospace or aeronautics, where typically one needs to monitor composite structures with varying mechanical properties and complex ge- ometries. This is particularly true in the case of multiscale composite materials, where anisotropy and material gradients may be present. Here, we provide an impact localization algorithm based on time reversal and laser vibrometry to cope with this type of complexity. The proposed approach is shown to be insensitive to local elastic wave velocity or geometrical features. The technique is based on the correlation of the measured impact response and a set of measured test data acquired at various grid points along the specimen surface, allowing high resolution in the determination of the impact point. We present both numerical finite element simulations and experimental measure- ments to support the proposed procedure, showing successful implementation on an eccentrically stiffened aluminium plate. The technique holds promise for advanced structural health monitoring, potentially in real time, of geometrically complex composite structures.